Stay strong, stay healthy: exploring a predictive model of psychological adaptation among Macau students studying in Mainland China within the postcolonial context - Feng, Haiyan; Zhang, Li (Frontiers in Psychology, 2024)
The prevailing research on adaptation primarily centres around the settlement of international students and immigrants in different cultural environments.However, there is a notable gap in understanding the intra-cultural adaptation process for individuals from postcolonial areas when relocating to their home country. The primary focus of the current study lies in constructing a predictive model that delineates the psychological adaptation experienced by Macau students studying in Mainland China. In total, two hundred and fifty-five Macau students completed a questionnaire which assessed variables falling into two categories: identity-related variables, such as language proficiency and identity, and intergroup-related variables, including intergroup contact and the quality of contact, and psychological adaptation.The findings from the present study revealed that identity and quality of contact continued to make significant contributions to psychological adaptation in intracultural environments as in inter-cultural environments, whereas language proficiency and intergroup contact were unrelated to psychological adaptation in intra-cultural adaptation. The present study extended the adaptation research by transporting hypotheses and findings from inter-cultural adaptation and testing their validity and applicability in postcolonial contexts. The findings also provided practical implications for Chinese education institutions and policy-makers.